Pengelolaan Dana Transfer dan Saldo Anggaran Lebih terhadap Belanja Modal Pemerintah Daerah Jawa Barat - Yuliansyah, Rahmat; Wasif, Said Khaerul; Pratama, Bayu; Krisnando, Krisnando (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to manage transfer funds and budget balances over capital expenditures in the West Java government. Method: This study uses a descriptive quantitative approach, measuring the management of transfer funds and excess budget balances in 27 districts/cities of West Java Province, 2017 – 2020 period. Using secondary data, data collection techniques using the documentation method through the websites djpk.kemenkeu.go.id and jabarprov.go.id, by testing all research samples. Results: The results show that the higher the transfer funds, the higher the local government's capital expenditure. The Excess Budget Balance (EBB) is decreasing, indicating a decline in government spending on capital. Limitation: Data collection during the Covid-19 pandemic resulted in limited research data obtained Contributions: Contributions, especially for the West Java regional government in managing transfer funds and SAL, as well as other regional governments and the research community.